Sistem Informasi Geografis Pemetaan Kantor Polisi Wilayah Kota Pekanbaru Provinsi Riau - Sukamto, Sukamto; Elfizar, Elfizar; Septiono, M Bimo (JUITA: Jurnal Informatika, 2018)
Abstract This research discusses about the Geographical Information System (GIS) mapping of Police Station in the city of Pekanbaru in Riau province. The absence of information about the existence of digital spread Police Station in the city of Pekanbaru that makes people want to take care of these needs when police agencies Pekanbaru be hampered because it takes a long time to find the police station .. It is underlying this research. SIG provides information to the public regarding the location and type Police Station in the city of Pekanbaru, so as the public will more easily find the Police Station to take care of the police office purposes. Besides GIS also helps the police Pekanbaru in determining the crime- prone locations occur so police can take preventive measures or planning to build a new police station. The information systems using programming language HTML, CSS, JQuery, PHP, XML, and Google Maps, and then MySQL as a database. To design the system using System Flowchart, Data Flow Diagram, and Entity Relation Diagram. Keywords : Mapping of Police station, Geographical Information System,